Asymptomatic hyperuricemia: secret relationships, invisible effects and potential complications - I. Yu. Golovach; Y. D. Yehudina; S. Kh. Ter-Vartanian (Научно-практическая ревматология)
Hyperuricemia is a widespread problem worldwide, the incidence of which is 16-17%. However, the significance of asymptomatic hyperuricemia - hyperuricemia without gout - continues to be discussed. Asymptomatic hyperuricemia leads to the deposition of monosodium urate crystal in the tissues, contributing to chronic inflammation. Intracellular urates inhibit the protein kinase associated with the main regulator of adenosine monophosphate, causing immune responses through long-term epigenetic modifications. And if intracellular urates have a prooxidant effect, soluble extracellular urates are biologically active and exliibilL' antioxidant properties with potentially anti-inflammatory effects. Based on population studies, asymptomatic hyperuricemia is associated with many comorbidities, including arterial hypertension, chronic kidney disease, coronary heart disease, and diabetes mellitus. However, these studies have a wide range of limitations, namely that most of them are retrospective, and some do not distinguish between patients with asymptomatic hyperuricemia and gout. Studies of therapeutic strategies show that lowering the urate level can reduce the risk of some of these comorbidities occurring or progressing. Thus, the accumulated data suggest that asymptomatic hyperuricemia contributes to the onset and progression of associated comorbidity, and that treatment of asymptomatic hyperuricemia can reduce risks. However, additional prospective studies are needed to accurately establish cause and effect relationships and support the decision about whether and in which patients with asymptomatic hyperuricemia it is worth initiating treatment that reduces urate levels. In addition, the available data confirm the neuroprotective effect of uric acid on cognitive function in patients with Alzheimer’s disease, Parkinson’s disease and vascular dementia, and hypouricemia is a risk factor for the more rapid progression of neurodegenerative diseases. This literature review will discuss some associations and potential mechanistic relationships between asymptomatic hyperuricemia and comorbid conditions.